Sistem Informasi Berbasis WebGIS untuk Data Spasial Akademik Pada Program Studi Penginderaan Jauh dan Sistem Informasi Geografis - Hidayatul Fikri; Eva Purnamasari (IDEALIS : InDonEsiA journaL Information System, 2026)
Study-program portals commonly present academic profiles, lecturer data, news, galleries, and facility information without linking facilities to geographic positions; consequently, academic information loses its spatial context. This study designed, implemented, and evaluated a WebGIS portal for the Remote Sensing and Geographic Information Systems Study Program. An R&D workflow covered problem identification, literature review, field acquisition, requirements analysis, system design, implementation, and evaluation. Coordinates and photographs were collected with KoboToolbox, verified in QGIS, and stored as point geometries in PostgreSQL/PostGIS; nonspatial content was managed through an administrator dashboard. The portal combines public information pages, an interactive map, facility markers, search, layer controls, categories, object details, and centralized content management. Evaluation involved one expert reviewing 35 functions, User Acceptance Testing with 30 students using 16 Likert items, and a limited security inspection. Thirty-three functions met the scenarios (94.29%), while UAT reached 2,045 of 2,400 points (85.21%; mean 4.26/5). No critical or high vulnerabilities were identified within the tested scope. Two WebGIS functions require improvement: HTTPS-based geolocation and complete object details. The research contribution is an integration model combining coordinate-based facility records, nonspatial academic content, and centralized administration in one study-program portal.